TRACHEAL STENOSIS IN CATS - Wahyudi , I Made Nanda; Putriningsih, Putu Ayu Sisyawati; Erawan, I Gusti Made Krisna (Buletin Veteriner Udayana, 2025)
Tracheal stenosis, a narrowing of the tracheal lumen, is a life-threatening condition that can cause severe airway obstruction. This case report describes the diagnosis and management of tracheal stenosis in a 9-month-old female cat presenting with chronic coughing, sneezing, and dyspnea. The study aimed to document clinical findings, diagnostic approaches, and therapeutic outcomes for feline tracheal stenosis. Clinical examination revealed dyspnea and a positive tracheal pinch reflex, while hematology showed lymphocytosis, thrombocytopenia, and elevated hemoglobin. Radiographic imaging confirmed tracheal narrowing. Treatment included an 8-day protocol of aminophylline (5 mg/kg p.o.), co-amoxiclav (12 mg/kg p.o.), methylprednisolone (2 mg/kg p.o.), bromhexine (0.2 mg/kg p.o.), and salbutamol-NaCl nebulization (2:9 mL), alongside isolation and owner education. Despite therapy, reevaluation after 8 days showed no clinical improvement, suggesting limited treatment efficacy. This case highlights the challenges in managing tracheal stenosis in cats and underscores the need for alternative therapeutic strategies. Further research into surgical interventions or advanced medical protocols is recommended for refractory cases.